PENERAPAN KOMUNIKASI INTERPERSONAL DOSEN IMPLIKASINYA PADA INTENSI ENTREPRENEUR MAHASISWA POLITEKNIK KESEHATAN ‘AISYIYAH BANTEN - Evi Avicenna Agustin; Halimah Tu’sadiah (Journal Of Applied Health Research And Development, 2021)
The midwife profession has a high enough interest, which makes the number of midwives increase rapidly, while employment is limited so that many midwifery graduates cannot be accommodated by existing formal sector jobs. One alternative solution to the problem is to create their own employment opportunities where the perpetrators will have the freedom to apply knowledge and skills according to the opportunities that exist as entrepreneurs, where this can be encouraged by providing entrepreneurship education for students. This study aims to determine and analyze the magnitude of the entrepreneurial intention of Aisyiyah's health polytechnic student which is implied by the communication relationship between lecturers and students in the interaction of their academic community. The approach used in this study is to use a quantitative approach, namely a research methodology that seeks to quantify data. and apply statistical analysis. Then, a specific hypothesis testing is conducted to determine whether the relationship or the significant effect between interpersonal communication between lecturers and students has implications for student entrepreneurial intentions. The results of the descriptive analysis illustrate that the low desire of students in entrepreneurship is that they are not brave enough to start a business and students are still not willing to mobilize their business potential, but descriptively it can also be explained that the strength of students' desire for entrepreneurship is shown by an attitude that never gives up and is brave. take planned risks. Associatively with the univariate correlation test, the results of the correlation are 0.591, a positive correlation value, this means that the interpersonal communication of the lecturers has a unidirectional relationship with the student entrepreneurial intentions. Meanwhile, based on the results of the output, it can be seen that the t value is greater than the t table (6,859> 1,950), this means that there are significant implications between the interpersonal communication of the lecturers and the entrepreneurial intentions of the Aisyiyah Banten Health Polytechnic students. pay more attention to the application of lecturers' interpersonal communication, especially the improvement in flexibility and rigidity training when communicating and remind lecturers through study programs not to always give an assessment of the way students communicate with lecturers so that students are not nervous when communicating with lecturers